The impact of the Covid-19 pandemic on postnatal anxiety and posttraumatic stress: analysis of two population-based national maternity surveys in England - Harrison, S; Quigley, MA; Fellmeth, G; Stein, A; Ayers, S; Alderdice, F (Elsevier, 2024)
Background Few studies have evaluated postnatal anxiety and posttraumatic stress (PTS) before and during the Covid-19 pandemic using comparable data across time. We used data from two national maternity surveys in England to explore the impact of the pandemic on prevalence and risk factors for postnatal anxiety and PTS.